2014
DOI: 10.4161/15384047.2014.956634
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of AXL, Lyn and p130Cas kinases block migration of triple negative breast cancer cells

Abstract: Abbreviations: AKT, RAC-a serine/threonine-protein kinase; FAK, focal adhesion kinase; EGFR, epidermal growth factor receptor; ELISA, enzyme-linked immunosorbant assay; Gas6, growth arrest specific 6; MAPK, mitogen activated protein kinases; PI3K, phosphatidylinositol 3-kinase; Pyk2, proline-rich tyrosine kinase 2; RTK, receptor tyrosine kinase; siRNA, short interfering RNA; TKI, tyrosine kinase inhibitor; TNBC, triple negative breast cancerBlocking the migration of metastatic cancer cells is a major goal in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
17
1
1
Order By: Relevance
“…Therefore, we treated Caliper cells with MPCD84111, which was characterized as an efficient inhibitor for AXL‐MET‐SRC by Penzes et al . (), and sunitinib, which was characterized as a multitargeted TKI, but without the impact on MET or SRC inhibition (Penzes et al ., ). We performed ATP assays 3 days after treatment of cells with increasing concentrations of MPCD84111 or sunitinib (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we treated Caliper cells with MPCD84111, which was characterized as an efficient inhibitor for AXL‐MET‐SRC by Penzes et al . (), and sunitinib, which was characterized as a multitargeted TKI, but without the impact on MET or SRC inhibition (Penzes et al ., ). We performed ATP assays 3 days after treatment of cells with increasing concentrations of MPCD84111 or sunitinib (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoprecipitation was performed as previously described (Torka, Penzes et al ., ). The home‐made clone 4G10 was used as antibody for phospho‐tyrosine precipitation in the concentration of 1 μg per 250 μg cell extract.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…4A). Our previous studies and others indicated that p130Cas is a proto-oncogene governing cell migration/invasion and its differential expression is related to cancer progression15162027. To test whether miR-24-3p regulates p130Cas expression, we investigated p130Cas expression in MCF7 cells after the transfection of miR-24-3p.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated that miR-24-3p is a novel regulator governing p130Cas expression. Since p130Cas plays an important role in cancer development, understanding the detailed mechanism of p130Cas regulation would provide a useful strategy for cancer therapy by targeting p130Cas2743.…”
Section: Discussionmentioning
confidence: 99%